Art Now '88. - Art Now '88 (Kobe : The Hyogo Prefectural Museum of Modern Art - The Asahi Shimbun, 1988)
Akioka, Miho ; Iwamoto, Takashi ; Okada, Takeshi ; Odanaka, Yasuhiro ; Kashio, Masaji ; Kawasaki, Koichi ; Kirihara, Yoshiyuki ; Kuno, Toshihiro ; Sugiura, Takao ; Sugiura, Misao ; Tanaka, Chiyoko ; Nakaji, Norio ; Nakamura, Michio ; Nagao, Hiroyuki ; Nagawara, Yuri ; Morimura, Yasumasa ; Yokoyama, Eiichi ; Katayama, Masahito ; Kawashima, Keiju ; Tsuzuki
Art Now '88, The Hyogo Prefectural Museum of Modern Art - The Asahi Shimbun, Kobe, 1988.2.20 - 3.21
kunstcatalogus